Incremental twisting fault tolerant control for hypersonic vehicles with partial model knowledge - Han, Tuo; Hu, Qinglei; Shin, Hyo-Sang; Tsourdos, Antonios; Xin, Ming (Institute of Electrical and Electronics Engineers (IEEE), 2021)
A passive fault tolerant control scheme is proposed for the full reentry trajectory tracking of a hypersonic vehicle in the presence of modelling uncertainties, external disturbances, and actuator faults. To achieve this goal, the attitude error dynamics with relative degree two is formulated first by ignoring the nonlinearities induced by the translational motions. Then, a multivariable twisting controller is developed as a benchmark to ensure the precise tracking task. Theoretical analysis with the Lyapunov method proves that the attitude tracking error and its first-order derivative can simultaneously converge to the origin exponentially. To depend less on the model knowledge and reduce the system uncertainties, an incremental twisting fault tolerant controller is derived based on the incremental nonlinear dynamic inversion control and the predesigned twisting controller. Notably, the proposed controller is user friendly in that only fixed gains and partial model knowledge are required.
Keywords: Hypersonic vehicle; reentry trajectory tracking; fault tolerant control; twisting control; actuator faults